2020
DOI: 10.1111/jfbc.13471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus plantarum fermented barley on plasma glycolipids and insulin sensitivity in subjects with metabolic syndrome

Abstract: Metabolic syndrome (MS), a kind of metabolic disorder, is characterized by abdominal obesity, insulin resistance, hyperglycemia, hyperlipidemia, and hypertension (Bai, Zhu, & Dong, 2018). The number of patients with MS is increasing yearly due to the changes in the diet structure and lifestyle at present (Taylor et al., 2013). The prevalence of MS is 32% in the United States and 25% in Europe and Latin America (Solis & Petrascheck, 2011). However, the incidence of MS is up to 30% in China (Zuo et al., 2009). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…The earliest paper was published in 2007, while the latest was in 2021. Most studies included were carried out in the Western countries, except for 10 studies that were mainly focused on Asian populations (two in China, two in Korea, one in Palestine, five in Iran) ( 29 , 31 , 37 , 40 , 44 , 53 , 55 , 56 , 58 , 66 ). Exceptionally, other researchers such as Bernini et al ( 52 ) utilized Lactobacillus as probiotic intervention and chose Bifidobacteriumlactis, while Leila et al ( 53 ) used Lactobacillus and Bifidobacterium for observation ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The earliest paper was published in 2007, while the latest was in 2021. Most studies included were carried out in the Western countries, except for 10 studies that were mainly focused on Asian populations (two in China, two in Korea, one in Palestine, five in Iran) ( 29 , 31 , 37 , 40 , 44 , 53 , 55 , 56 , 58 , 66 ). Exceptionally, other researchers such as Bernini et al ( 52 ) utilized Lactobacillus as probiotic intervention and chose Bifidobacteriumlactis, while Leila et al ( 53 ) used Lactobacillus and Bifidobacterium for observation ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…Exceptionally, other researchers such as Bernini et al ( 52 ) utilized Lactobacillus as probiotic intervention and chose Bifidobacteriumlactis, while Leila et al ( 53 ) used Lactobacillus and Bifidobacterium for observation ( 52 ). For microbial metabolites, one study used whey protein ( 27 ), another study utilized Lactobacillus plantarum fermented barley ( 66 ), which is abundant of biologically active ingredients, and other studies employed niacin as bacterial metabolites. Prebiotics were implicated in researches, such as isomaltulose ( 46 ), glucose polysaccharide ( 37 ), and resistant starch ( 24 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37,39,40,42,[44][45][46][51][52][53]55,56 Eight studies were conducted in adults with overweight and/or obesity, [42][43][44][45][46]49,50,56 seven in untrained and non-athletic healthy populations, 37,40,41,51,54,55,59 one in resistance-trained individuals, 53 one in individuals with metabolic syndrome and type 2 diabetes 48 or hypertension, 60 one in people with frailty, 38 one in people with low bone mineral density, 58 one in patients with chronic heart failure, 57 one in participants with non-displaced distal radius fracture, 47 one in triathletes 39 and one in volleyball and soccer players. 52 Eleven studies had a treatment duration of 12 weeks, [41][42][43][44][45][46]49,50,54,55,57 three of ...…”
Section: Resultsmentioning
confidence: 99%
“…The pigs fed with LAB--fermented feed had a lower caecum abundance of taxa negatively associated with pig growth, including Megasphaera, Bifidobacterium, and Streptococcus [Torres-Pitarch et al, 2020]. A single-blinded and parallel clinical trial study where subjects were eating fermented barley-wheat flour noodle for ten weeks showed a lower level of fasting blood glucose, HbA1c, and triglycerides in subjects with the metabolic syndrome [Pan et al, 2020]. Moreover, improved satiety and the reduction of fat mass, without the loss of lean mass, was observed in a group consuming fermented noodles.…”
Section: Probiotic Activitymentioning
confidence: 99%